Effect of synthesis conditions and composition on structural and phase states and electrical properties of nanogranular (FeCoZr)x (PZT)100-x films (30 ≤ x ≤ 85 at.%) - Julia A. Fedotova (Pensoft Publishers, 2021)
Granular films containing Fe50Co50Zr10 alloy nanoparticles inside Pb0,81Sr0,04(Na0,5Bi0,5)0,15(Zr0,575Ti0,425)O3 (PZT) ferroelectric matrix possess a combination of functional magnetic and electrical properties which can be efficiently controlled by means of external electric or magnetic fields. The formation of the required granular structure in PZT matrix is only possible if synthesis is carried out in an oxygen-containing atmosphere leading to substantial oxidation of metallic nanoparticles. Thus an important task is to study the oxidation degree of metallic nanoparticles depending on synthesis conditions and the effect of forming phases on the electrical properties of the films. The relationship between the structural and phase state and electrical properties of granular FeCoZr)x (PZT)100-x films (30 ≤ x ≤ 85 at.%) synthesized in an oxygen-containing atmosphere at the oxygen pressure PO in a range of (2.4–5.0) · 10–3 Pa has been studied using X-ray diffraction, EXAFS and four-probe electrical resistivity measurement. Integrated comparative analysis of the structural and phase composition and local atomic order in (FeCoZr)x (PZT)100-x films has for the first time shown the fundamental role of oxygen pressure PO during synthesis on nanoparticle oxidation and phase composition. We show that the oxygen pressure being within PO = 3.2 · 10–3 Pa an increase in x leads to a transition from nanoparticles of Fe(Co,Zr)O complex oxides to a superposition of complex oxides and a-FeCo(Zr,O) ferromagnetic nanoparticles (or their agglomerations). At higher oxygen pressures РО = 5.0 · 10–3 Pa the nanoparticles undergo complete oxidation with the formation of the (FexCo1-x)1-δO complex oxide having a Wurtzite structure. The forming structural and phase composition allows one to explain the observed temperature dependences of the electrical resistivity of granular films. These dependences are distinguished by a negative temperature coefficient of electrical resistivity over the whole range of film compositions at a high oxygen pressure (РО = 5.0 · 10–3 Pa) and a transition to a positive temperature coefficient of electrical resistivity at a lower oxygen pressure (РО = 3.2 · 10–3 Pa) in the synthesis atmosphere and x > 69 at.% in the films. The transition from a negative to a positive temperature coefficient of electrical resistivity which suggests the presence of a metallic contribution to the conductivity is in full agreement with the X-ray diffraction and EXAFS data indicating the persistence of unoxidized a-FeCo(Zr,O) ferromagnetic nanoparticles or their agglomerations.